2013
DOI: 10.4038/jas.v8i1.5373
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional yield and economic responses of sunflower (Helianthus annuus l.) to integrated levels of nitrogen, sulphur and farmyard manure

Abstract: The field experiments were conducted at Agronomy Farm of Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir during 2009 and 2010, to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
6
10
0
Order By: Relevance
“…This might be due to synthesis of higher amount of sulphur containing amino acids and fatty acid (conversion of acetyl Co-A to malonyl Co-A) resulting from increased activity of thiokinase enzyme due to S supply. Similar results were reported by Poonia (2000); Rasool et al (2013) and Sheoran et al (2014). ).95 t ha -1 oil yield was obtained in hybrid Super-48 which was followed by Super-90 (0.83 t ha -1 ).…”
Section: Oil Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…This might be due to synthesis of higher amount of sulphur containing amino acids and fatty acid (conversion of acetyl Co-A to malonyl Co-A) resulting from increased activity of thiokinase enzyme due to S supply. Similar results were reported by Poonia (2000); Rasool et al (2013) and Sheoran et al (2014). ).95 t ha -1 oil yield was obtained in hybrid Super-48 which was followed by Super-90 (0.83 t ha -1 ).…”
Section: Oil Yieldsupporting
confidence: 89%
“…Dry matter (Table 2) also increased at a rate of around 3.5% in the period between 30 to 45 DAS that followed same trend as that of plant height. This, results were confirmed by earlier worker Rasool et al (2013). Hybrid Super-48 recorded in highest dry matter accumulation of 133.22 which was superior over the others.…”
Section: Dry Matter Productionsupporting
confidence: 84%
“…6 Research elsewhere has shown that the application of 10 t/ha and 20 t/ha farmyard manure improved sunflower grain yield. 7 Recently Materechera 8 reported improved aggregate stability, reduced soil strength and bulk density and increased bambara nut (Voandzeia subterranean L.) growth and yield after applying 5 t/ha of cattle manure on a hard setting and crusting chromic Luvisol in South Africa. Dunjana 9 observed in clayey soils that infiltration rates were increased by 30% with 25 t/ha cattle manure applications over control, while no changes in steady state infiltration rates were observed with manure application on sandy soils after 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, information is lacking on the response of sunflower to organic fertilizer application in humid tropical Africa. Recent work in India reported linear increase in seed yield as farmyard manure rate increased from 10 to 20 ton/ha, suggesting that an additional increase in seed yield with increase in rate of farmyard manure (Rasool et al, 2013). Similarly, plant population density (Olowe, 2005;Petcu et al, 2010) and planting ratio (Shakuntula et al, 2012) studies also indicated varying results in different locations.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier research works on sunflower agronomy in the tropics reported varying optimum rates of nitrogen fertilizer to be 60 kg N/ ha in Nigeria , 80 kgN/ha in India (Rasool et al, 2013), 150 kgN/ha at Islamabad, Pakistan (Bakht et al, 2010) and 180 kgN/ha at Faisalabad, Pakistan (Nasim et al, 2012b). Sunflower growers rarely apply organic fertilizers to sunflower despite the inherent advantage (slow nutrient release and potential improvement of soil structure and water holding capacity) of organic plot compared with the conventional plot (Posner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%